Translating next generation sequencing to practice: Opportunities and necessary steps. Issue 4 (15th May 2013) - Kamalakaran, Sitharthan; Varadan, Vinay; Janevski, Angel; Banerjee, Nilanjana; Tuck, David; McCombie, W. Richard; Dimitrova, Nevenka; Harris, Lyndsay N.
Abstract : Next‐generation sequencing (NGS) approaches for measuring RNA and DNA benefit from greatly increased sensitivity, dynamic range and detection of novel transcripts. These technologies are rapidly becoming the standard for molecular assays and represent huge potential value to the practice of oncology. However, many challenges exist in the transition of these technologies from research application to clinical practice. This review discusses the value of NGS in detecting mutations, copy number changes and RNA quantification and their applications in oncology, the challenges for adoption and the relevant steps that are needed for translating this potential to routine practice. Highlights: Next Generation sequencing (NGS) enables measurement of clinically relevant mutations, DNA copy number and gene expression. We review diagnostic, prognostic and therapy selection applications of NGS for different types of cancer. We discuss technology challenges that need to be overcome for implementing NGS into widespread clinical use. We discuss education, regulatory framework, storage, privacy and confidentiality of genomic data to enable adoption.